Nonmonotonic aftereffect measurements in perpendicular synthetic ferrimagnets - Fache T. (2018)
H.S.T. thanks the Peruvian Doctoral Scholarship Program of CIENCIACTIVA (CONCYTEC) for financial support under Grand No. 218-2014-FONDECYT. J.Q.-M. and C.V.L. are grateful to CIENCIACTIVA (CONCYTEC) for financial support through the Excellence Centers Program. C.H.W.B. acknowledges financial support from EPSRC (Grant No.EP/J00412X/1). R.M. thanks to Institute Jean Lamour Nancy for financial support of visiting professorship. This work was supported by Ministry of Education and Science of the Russian Federation (grant 3.1992.2017/4.6). This work was also partly supported by the French PIA project “Lorraine Université d’Excellence,” reference ANR-15-IDEX-04-LUE. by the ANR-NSF Project, ANR-13-IS04-0008-01, COMAG. This work was also partly funded by the ANRT, under the CIFRE convention No. 2016/1458.